(untitled) - Spellerberg, Ian F. (London, 1992)
This book, previously published in hardback, has now been republished in paperback and added to the growing number of titles in Chapman & Hall's Conservation Biology Series. Evaluation and Assessment for Conservation contains pertinent examples and case studies from around the world illustrating the issues faced by conservationists. In addition, it summarizes a very large amount of material from the scientific literature.
Keywords: Bảo tồn thiên nhiên,Đánh giá phong cảnh,Nature conservation,Landscape assessment; Đánh giá,Evaluation